Pengukuran Sound Pressure Level (SPL) dalam kabin mobil dengan menggunakan SEA Model - Al Munawir; Murhaban Murhaban; Zulfan Zulfan (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2020)
Statistical energy analysis (SEA) is a well-known method to analyze the flow of acoustic and vibration energy in a complex structure. For an acoustic space where significant absorptive materials are present, direct field component from the sound source dominates the total sound field rather than a reverberant field, where the latter becomes the basis in constructing the conventional SEA model. Such environment can be found in a car interior and thus a corrected SEA model is proposed here to counter this situation. The model is developed by eliminating the direct field component from the total sound field and only the power after the first reflection is considered. A test car cabin was divided into two subsystems and by using a loudspeaker as a sound source, the power injection method in SEA was employed to obtain the corrected coupling loss factor and the damping loss factor from the corrected SEA model. These parameters were then used to predict the sound pressure level in the interior cabin using the injected input power from the engine. The results show satisfactory agreement with the directly measured SPL.Keywords : Statictical Energy Analysis (SEA), Sound Pressure level (SPL), DLF and CLF